Recently I asked a question about the sum of $\sum_{k=0}^n {n\choose k}^p f\left(k\right)$. Then, I was thinking of the case when $p=-1, f\left(x\right)=1$, which is $\sum_{k=0}^n \dfrac{1}{n\choose k}=\dfrac{1}{n\choose 0}+\dfrac{1}{n\choose 1}+\cdots+\dfrac{1}{n\choose n}$. I have substituted $n=0,1,\cdots,7$ and we get $1,2,\dfrac{5}{2},\dfrac{8}{3},\dfrac{8}{3},\dfrac{13}{5},\dfrac{151}{60},\dfrac{256}{105}$, which seems that there has no obvious sequence. Then, I tried to use Wolfram Alpha to find the answer. It gets no answer when I search $\sum_{k=0}^n \dfrac{1}{n\choose k}$, but when we change $\dfrac{1}{n\choose k}$ into $\dfrac{k!\left(n-k\right)!}{n!}$ and take out the $\dfrac{1}{n!}$, we get $$\dfrac{1}{n!}\sum_{k=0}^n k!\left(n-k\right)!$$ , whose answer can be found by Wolfram Alpha! However, the result is this: $$-\dfrac{i2^{-n-1}\Gamma\left(n+2\right)\left(\pi-i\mathrm{B}_2 \left(n+2,0\right)\right)}{n!}=-2^{-n-1}\left(n+1\right)\left(\mathrm{B}_2 \left(n+2,0\right)+i\pi\right)$$

I was really surprised! How come "$i$" is being here! And what's the "$\mathrm{B}_2$" means? I found that it is called Incomplete Beta Function which has the definition: $$\mathrm{B}_z\left(a,b\right)\equiv\int_0^z x^{a-1} \left(1-x\right)^{b-1}dx$$ So, I tried to find $\mathrm{B}_2 \left(n+2,0\right)$. Substitute $z=2, a=n+2, b=0$ into the definition and it gives: $$\mathrm{B}_2 \left(n+2,0\right)=\int_0^2 \dfrac{x^{n+1}}{1-x}dx$$ However, $\dfrac{x^{n+1}}{1-x}$ is not continuous at $x=1$ and I was stuck at this integral. I thought it may have some relationship with the $i\pi$

Conclusion: There are some questions I want to know, please answer me if you know.

$1$. Explain $\dfrac{1}{n!}\sum_{k=0}^n k!\left(n-k\right)!=-2^{-n-1}\left(n+1\right)\left(\mathrm{B}_2 \left(n+2,0\right)+i\pi\right)$
$2$. Solve the integral $\int_0^2 \dfrac{x^{n+1}}{1-x}dx$ and find the answer

$3$. (Optional) Better way to find the sum $\sum_{k=0}^n \dfrac{1}{n\choose k}$

Thank you!


$$\sum_{k=0}^{n}\binom{n}{k}^{-1} = \frac{1}{\Gamma(n+1)}\sum_{k=0}^{n}\Gamma(k+1)\Gamma(n-k+1)=\frac{\Gamma(n+2)}{\Gamma(n+1)}\sum_{k=0}^{n}B(k+1,n-k+1)$$ using the integral representation for the Beta function this is turned into $$\begin{eqnarray*}(n+1)\int_{0}^{1}\sum_{k=0}^{n}x^{k}(1-x)^{n-k}\,dx &=&(n+1)\int_{0}^{1}\frac{x^{n+1}-(1-x)^{n+1}}{2x-1}\,dx\\&=&\frac{n+1}{2}\int_{-1}^{1}\frac{\left(\frac{1+z}{2}\right)^{n+1}-\left(\frac{1-z}{2}\right)^{n+1}}{z}\,dz\end{eqnarray*}$$ or $$\begin{eqnarray*}\frac{n+1}{2^{n+2}}\int_{-1}^{1}\left[(1+z)^{n+1}-(1-z)^{n+1}\right]\frac{dz}{z}&=&\frac{n+1}{2^{n}}\int_{0}^{1}\sum_{k\leq n/2}\binom{n+1}{2k+1}z^{2k}\,dz\\&=&\frac{n+1}{2^n}\sum_{k\leq n/2}\binom{n+1}{2k+1}\frac{1}{2k+1}.\end{eqnarray*}$$

  • $\begingroup$ Is there a mistake at the first integral in the sixth line? It should be $\int^1_{-1}$, right? $\endgroup$ – Isaac YIU Math Studio Aug 30 at 11:33
  • $\begingroup$ @IsaacYIUMathStudio: everything should be correct, at some point I exploited the fact that the integral over $(-1,1)$ of an even function is just twice the integral over $(0,1)$. $\endgroup$ – Jack D'Aurizio Aug 30 at 11:39
  • $\begingroup$ No, I mean that the integral after "or", the upper number should be 1 $\endgroup$ – Isaac YIU Math Studio Aug 30 at 11:40
  • $\begingroup$ @IsaacYIUMathStudio: oh, that. Of course, now fixed. $\endgroup$ – Jack D'Aurizio Aug 30 at 11:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.